Creativity and Entrepreneurship: A Regional Analysis of New Firm Formation - Sam Youl Lee; Richard Florida; Zoltán J. Ács (Max Planck Institute for Research into Economic Systems, 2004)
Understanding the factors that promote or mitigate new firm birth is crucial to regional economic development efforts, since a high level of new firm creation significantly contributes to regional economic vitality and is a major signal of a dynamic economy. The literature suggest that various factors such as unemployment, population density/growth, industrial structure, human capital, the availability of financing, and entrepreneurial characteristics significantly influence regional variation in new firm birth rates.
Keywords: 330; Unternehmensgründung; Kreativität; Humankapital; Soziale Beziehungen; Regionale Disparität; Schätzung; USA